Case Report: Durable complete response to antigen-specific cytotoxic T lymphocyte therapy in advanced EGFR-TKI resistant lung adenocarcinoma: a case of adoptive cellular immunotherapy overcoming acquired targeted resistance - Fu, Chenghao; Bian, Chengyu; Zhu, Weiyou; Du, Haonan; Han, Linrui; Zhu, Jian; Wang, Jun; Cao, Lei (Frontiers in Immunology, 2025)
Adoptive cell therapy (ACT), an important component of tumor immunotherapy, achieves precise anti-cancer effects by reinfusing in vitro-processed immune cells, providing a new option for advanced tumor patients with resistance to chemotherapy or targeted therapy. Among them, antigen-specific cytotoxic T lymphocyte (ACTL) therapy innovatively integrates the natural expansion advantage of tumor-infiltrating lymphocytes (TILs) and the precise antigen-presenting mechanism of recombinant adeno-associated virus-transfected dendritic cells (rAAV-DCs), becoming a research focus. This case report describes a patient with IVa stage advanced lung adenocarcinoma with multiple intrapulmonary metastases carrying an epidermal growth factor receptor (EGFR) exon 19 deletion mutation. After receiving treatment with the third-generation EGFR-tyrosine kinase inhibitor (EGFR-TKI) drug osimertinib, the patient developed acquired resistance with unknown mechanisms and was in an immune-suppressed state. Subsequently, the patient received ACTL therapy and ultimately achieved a clinical complete response (cCR) and maintained it for six years of follow-up. This case is the first to report that ACTL therapy has achieved “clinical cure” in a patient with acquired EGFR-TKI resistance, indirectly suggesting the underlying mechanism of this therapy in reshaping the tumor immune microenvironment (TME). It illustrates that ACTL, as a novel cellular immunotherapy with both target precision and immune balance, has demonstrated potential in overcoming targeted resistance in advanced lung cancer and inducing deep remission.